2019
DOI: 10.4269/ajtmh.18-0152
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Cytomegalovirus from Symptomatic Infected Neonates in Iraq

Abstract: . Among all other viruses, human cytomegalovirus (HCMV) is the most frequent cause of congenital infection worldwide. Strain variation in HCMV may predict severity or outcome of congenital HCMV disease. Previous studies have associated a particular genotype with specific sequelae or more severe illness, but the results were contradictory. There are no previous studies addressing the genotype of HCMV in Iraq. Therefore, the present study is aimed at molecular detection and genotyping of HCMV isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
(54 reference statements)
0
8
0
1
Order By: Relevance
“…Compared to a single gB genotype infection, mixed gB genotype infections are frequently reported in organ/bone marrow transplant recipients and AIDS patients [105,118,125,128,129,152]. Multiple studies have also demonstrated that mixed infections are able to be transmitted in utero [63,68,[74][75][76][77]109,122,134,137,138,141]. Although there is no established association between single genotype infections and disease outcomes, patients with mixed gB genotype infections have been reported to have faster disease progression or higher viral loads [83,97,102,144].…”
Section: Gbmentioning
confidence: 99%
“…Compared to a single gB genotype infection, mixed gB genotype infections are frequently reported in organ/bone marrow transplant recipients and AIDS patients [105,118,125,128,129,152]. Multiple studies have also demonstrated that mixed infections are able to be transmitted in utero [63,68,[74][75][76][77]109,122,134,137,138,141]. Although there is no established association between single genotype infections and disease outcomes, patients with mixed gB genotype infections have been reported to have faster disease progression or higher viral loads [83,97,102,144].…”
Section: Gbmentioning
confidence: 99%
“…The potential significant differences in genotype distribution found in different studies may be based on geographical distribution, patient population, and CMV tissue tropism 25 26 Ignoring these factors to investigate the possible relationship between genotype and clinical features may lead to wrong conclusions. We systematically reviewed some literature concerning the distributions of gB genotype among Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, other studies confirmed that gB3 and gB2 were the most prevalent genotypes in the sera of AIDS patients and HCMV-infected neonates and a high incidence of mixed infection with the gB1 and gB3 genotypes. 34,35 HCMV is known to be responsible for a variety of diseases, for example, in the oral cavity; persistent and atypical mucosal ulcers and xerostomia potentially accompanied by salivary gland dysfunction. 36 The prevalence of xerostomia among HIV-infected patients, has been estimated to range from 1.2 to 40% 22 and reduced salivary flow rate occurs in 2-30% of subjects.…”
Section: Discussionmentioning
confidence: 99%